Dermatomyositis is associated with an increased risk of cardiovascular and cerebrovascular events: a Taiwanese population‐based longitudinal follow‐up study. (25th April 2013) - Lai, Y.‐T.; Dai, Y.‐S.; Yen, M.‐F.; Chen, L.‐S.; Chen, H.‐H.; Cooper, R.G.; Pan, S.‐L.
Summary: Background While the chronic inflammation related to autoimmune diseases is known to be associated with an increased cardiovascular risk, much less is known about cerebrovascular risks. Objectives The present population‐based, age‐ and sex‐matched follow‐up study was undertaken to investigate the risks of acute myocardial infarction (AMI) and ischaemic stroke in patients with dermatomyositis (DMS). Methods In total 907 patients with DMS were enrolled and compared with a non‐DMS control group consisting of 4535 age‐ and sex‐matched, randomly sampled subjects without DMS. The AMI‐free and ischaemic stroke‐free survival curves were generated using the Kaplan–Meier method. Cox proportional hazard regression was used to estimate the DMS‐associated risks of AMI and ischaemic stroke. Results During the 2‐year follow‐up period, 14 patients with DMS (1·5%) and 18 patients in the non‐DMS control group (0·4%) suffered AMIs. The crude hazard ratio (HR) for suffering an AMI in patients with DMS compared with subjects in the non‐DMS group was 3·96 [95% confidence interval (CI) 1·97–7·96, P = 0·0001], while the adjusted HR was 3·37 (95% CI 1·67–6·80, P = 0·0007), after taking into account demographic characteristics and cardiovascular comorbidities. During the same follow‐up period, 46 patients (5·1%) and 133 subjects in the control group (2·9%) developed ischaemic strokes. The crude HR for developing an ischaemic stroke in patients with DMS compared with subjects in the non‐DMS group was 1·78 (95% CI 1·27–2·49, P = 0·0007), and the adjusted HR was 1·67 (95% CI, 1·19–2·34, P = 0·0028). Conclusions These findings suggest that DMS is associated with an increased risk of cardiovascular and cerebrovascular events. Abstract : What's already known about this topic? Connective‐tissue disorders, such as rheumatoid arthritis, Sjögren syndrome, systemic lupus erythematosus and primary vasculitis have been linked to an increased risk of cardiovascular disease. Data on any association between dermatomyositis and cardiovascular or cerebrovascular disease is sparse. What does this study add? This population‐based, age‐ and sex‐matched longitudinal follow‐up study shows that dermatomyositis is associated with increased risks of acute myocardial infarction and ischaemic stroke.